Protocolo de higienização bucal em pacientes portadores de doenças crônicas domiciliados: uma abordagem interdisciplinar - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Oral hygiene is an important factor to be considered in patients with chronic diseases. The increase in the longevity of population makes it necessary to develop strategies in home care by dentists and other health professionals. This study aimed to propose a home professional oral hygiene protocol and evaluate its positive and negative impacts. A total of 100 patients were selected and subsequently submitted to the eligibility criteria. They were stratified and divided into an experimental group and a control group. The patients underwent an initial clinical examination and afterwards a collection of biological material, an assessment of salivary pH and verification of the degree of halitosis both before and after the protocol being applicated. The impact of oral health on quality of life of patients was assessed using the OHIP-14 questionnaire and general quality of life parameters using the Improvement Wheel tool. As a result, there was a significant decrease in CFUs / 3x10ˉ³ for the control group, normalization of pH and decrease in the degree of halitosis (p <0.0001). For the experimental group, significant differences were found for pH and halitosis (p <0.0001) while for UFCs / 3x10ˉ³ there were no significant differences (p> 0.05). High scores were not highlighted in the OHIP-14 questionnaire for the influence of oral health on the quality of life of patients at home, however, the discomfort related to maladjusted prostheses and impacts on the diet was evidenced. For the Improvement Wheel, there were significant differences before and after the application of the tool for almost all parameters evaluated (p <0.05), which can be an aid to identify problems and develop solutions for patients and their caregivers. The oral hygiene protocol may be an effective alternative to be taught and applied in the care of the patient at home.
Keywords: Higiene bucal; Microbiologia; Qualidade de vida; Interdisciplinar; Visita domiciliar; Oral hygiene; Microbiology; Quality of life; Interdisciplinary; Home visit; CNPQ::CIENCIAS DA SAUDE